2018
DOI: 10.7567/apex.11.110101
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on steep-subthreshold-slope negative-capacitance field-effect transistor

Abstract: In today’s highly information-oriented society, a continuously increasing number of computing devices are needed in the Internet-of-Things (IoT) era, from high-end servers in cloud to sensor node devices in edge. Under the constraint of power consumption, energy-efficient computing is necessary to enable low-power operation and implement emerging algorithms such as machine learning. A steep-subthreshold-slope (SS) transistor can be a next-generation device technology platform for highly energy-efficient comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 99 publications
0
40
0
Order By: Relevance
“…It has been found that when the capacitance parameters satisfy the condition | C i | > C c , a dielectric matching can be reached, and the hysteresis in the I DS – V GS curve is absent. [ 43 ] In other word, we need to break the dielectric matching effect to obtain a large‐enough hysteresis for high‐performance ferroelectric memories. Hence, confirming the dual‐gated coupling is required.…”
Section: Figurementioning
confidence: 99%
“…It has been found that when the capacitance parameters satisfy the condition | C i | > C c , a dielectric matching can be reached, and the hysteresis in the I DS – V GS curve is absent. [ 43 ] In other word, we need to break the dielectric matching effect to obtain a large‐enough hysteresis for high‐performance ferroelectric memories. Hence, confirming the dual‐gated coupling is required.…”
Section: Figurementioning
confidence: 99%
“…For NEM‐FET, speed is limited to MHz due to the moving of heavy mass. Recently, negative capacitance (NC) effect in an FE/dielectric gate stack is proposed as a possible solution to break the 60 mV dec −1 limitation . HfO 2 ‐based FE materials are particularly attractive because of: 1) excellent CMOS‐compatibility by atomic layer deposition (ALD), 2) scalability to ultrathin thickness, 3) no sacrifice of I on , and 4) potential GHz operation…”
mentioning
confidence: 99%
“…However, the leakage currents of transistors and memory have not been reduced at the same rate due to the fundamental thermionic limit, known as the Boltzmann Tyranny. [3,4] As a result, the heat generation and power consumption due to leakage current per chip become quite high, so that the development of ultralow-power semiconductor devices with reduced energy consumption is urgently required. [5] In particular, to enable low power operation of a field-effect transistor, it is necessary to control the channel surface potential (ψ s ) according to the gate voltage in order to minimize the leakage current in the weak inversion state.…”
Section: Doi: 101002/admi202001356mentioning
confidence: 99%